Detection of multidrug-resistant Staphylococcus aureus isolated from dairies milk in Medowo Village of Kediri District, Indonesia - GIOVANNI DWI SYAHNI PUTRA; ASWIN RAFIF KHAIRULLAH; MUSTOFA HELMI EFFENDI; MOCHAMAD LAZUARDI; SHENDY CANADYA KURNIAWAN; DANIAH ASHRI AFNANI; OTTO SAHAT MARTUA SILAEN; YUSAC KRISTANTO KHODA WARUWU; SAUMI KIREY MILLANNIA; AGUS WIDODO; SAFIRA RAMADHANI; MUHAMMAD THORIQ IHZA FARIZQI; KATTY HENDRIANA PRISCILIA RIWU (Society for Indonesian Biodiversity, 2023)
Abstract. Putra GDS, Khairullah AR, Effendi MH, Lazuardi M, Kurniawan SC, Afnani DA, Silaen OSM, Waruwu YKK, Millannia SK, Widodo A, Ramadhani S, Farizqi MTI, Riwu KHP. 2023. Detection of multidrug-resistant (MDR) Staphylococcus aureus isolated from dairies milk in Medowo Village of Kediri District, Indonesia. Biodiversitas 24: 423-430. Bacterial resistance has emerged as a major concern in dairy farms in Indonesia due to the pervasive usage of antibiotics. Furthermore, no specific research has been done to explain the prevalence of Staphylococcus aureus in isolated milk from dairy cows in Kediri, particularly in Medowo Village, and their antibiotic resistance. Moreover, to control the emergence of diseases in humans brought on by dairy cow's milk or infections transmitted through milk, additional research on the prevalence and resistance of bacteria in dairy farms in the Kediri district is urgently required. In Medowo, the Village Kandangan of District, Kediri Regency, Indonesia, 100 dairy cow's milk samples were taken from farms in numerous hamlets. The Kirby-Bauer method performed an antibiotic sensitivity test using disk diffusion. The sensitivity test was attached with antibiotic discs on tetracycline, penicillin, gentamicin, erythromycin, and cefoxitin. According to sample evaluation results, S. aureus was detected in 94 (94%) of the 100 isolated milk samples based on morphological culture features, Gram staining, and biochemical assays. According to the profile of antibiotic resistance derived from the findings of the S. aureus antibiotic resistance test, 23 isolates (24.47%) were proven to be multidrug-resistant (MDR) because they were resistant to three to four classes of antibiotics. The use of antibiotics typically rises in response to an increase in the prevalence of disease in cattle, which could lead to higher levels of antibiotic residue in milk and possibly higher levels of bacterial resistance to antibiotics. Therefore, dairy farming requires methods for prudently and correctly employing antibiotics.